Communication - Denny, Richard; Lake, Nick; Turner, Barry; Gawith, Paul ([S.l.] : Man Management Ltd. [production company] ; Kuala Lumpur : First Training [distributor])
Described the roles of communication. Characters of communication and types of communication
Camera, Mark Lipscomb ; sound supervisor, Bill Cadman ; lighting director, Nigel Fisher
Keywords: Business communication; Communication in management; Communication